Analytical treatment of regularized Prabhakar fractional differential equations by invariant subspaces - Chu, Y. -M.; İnç, Mustafa; Hashemi, M. S.; Eshaghi, S. (Springer Heidelberg, 2022)
This work is devoted to the time-fractional differential equations with the regularized Prabhakar derivative and their analytical solutions. We generalize the invariant subspace method to find the exact solutions of such equations. Then, we apply this method to obtain the exact solutions of different time-fractional nonlinear differential equations including the regularized Prabhakar derivative.
Keywords: Regularized Prabhakar derivative; Invariant subspace method; Exact solution